1996
DOI: 10.1161/01.hyp.28.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor mRNA Expression in the Developing Cardiopulmonary System of the Rat

Abstract: Recent studies have shown that angiotensin II has a trophic action on the heart. The presence of two types of angiotensin II receptors, type 1 (AT1) and type 2 (AT2), has been reported in the rat heart. This in situ hybridization study describes the tissue and cell location of AT2 receptor mRNA in the developing rat cardiopulmonary system, from 15 days of gestation to adulthood. Expression of AT1A receptor mRNA was studied in parallel for direct comparison. The aortic arch and pulmonary artery expressed high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
66
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 28 publications
8
66
1
1
Order By: Relevance
“…1,2 The AT 2 receptor is abundantly and widely expressed in fetal tissues, but its expression declines rapidly after birth. 3,4 Interestingly, the AT 2 receptor is reexpressed in certain pathological conditions such as inflammation and vascular injury. 1,2 These findings suggest that the AT 2 receptor plays an important role not only in vasculogenesis but also in vascular remodeling.…”
mentioning
confidence: 99%
“…1,2 The AT 2 receptor is abundantly and widely expressed in fetal tissues, but its expression declines rapidly after birth. 3,4 Interestingly, the AT 2 receptor is reexpressed in certain pathological conditions such as inflammation and vascular injury. 1,2 These findings suggest that the AT 2 receptor plays an important role not only in vasculogenesis but also in vascular remodeling.…”
mentioning
confidence: 99%
“…In a previous in situ hybridization study analysis in rats showed that AT 2 mRNA was detected in bronchi and trachea but very little in stroma in the E19 fetal and new born pups, whereas the expression levels of AT 2 mRNA in the adult rat lung is very low or negligible (Shanmugam et al 1996). In adult human lung tissues, AT 2 protein expression was detected in brush borders of bronchial epithelium by immunohistochemical analysis with anti-rabbit anti-AT 2 antiserum (Bullock et al 2001).…”
Section: Discussionmentioning
confidence: 93%
“…AT2 receptors are highly expressed in a variety of tissues in developing embryos, but AT2 expression declines after birth [65,66]. Until now, the range of AT2-dependent functions and AT2-linked intracellular signaling events are still not completely understood [67].…”
Section: Nhe3mentioning
confidence: 99%